'The Poor Man's Son' and the Corruption of Our Moral Sentiments: Commerce, Virtue and Happiness in Adam Smith. Issue 1 (March 2017) - Hill, Lisa
Abstract : In order to operate effectively, modern capitalism depends on agents who evince a rather morally undemanding type of moral character; one that is acquisitive, pecuniary, recognition-seeking and merely prudent. Adam Smith is considered to have been the key legitimiser of this archetype. In this paper I respond to the view that Smith is actually sceptical about the value of material acquisition and explore whether he really believed that the pursuit of tranquillity and virtue—especially beneficence—offers a superior route to happiness than the commercial world of materialist acquisition. I approach these issues partly by considering the roles of beneficence and sympathy in Smith's system and partly by analysing the story of 'The Poor Man's Son' related in Book IV of The Theory of Moral Sentiments . As he narrates this story, Smith seems highly critical of the unrelenting drive for worldly success. But what is the real moral of the story? Should people contain their ambition for recognition and material success and pursue tranquillity and virtue instead? I suggest that Smith's discussion in and around the story of 'The Poor Man's Son' points to a significant tension between his personal ideal of happiness and his observations and recommendations as a social scientist.